A study on the headteachers’ perceptions of practicing transformational leadership, Malaysia - Salleh, Mohamad Johdi; Razikin, Mohyani; Saidova, Parvina (2009)
The objectives of this study is to examine the headteachers’ perceptions of transformational leadership and their practices according to gender, age, ethnic group, academic qualifications, working experience, location of the school, type of school, school’s grade and number of students. The study was based on the survey of one-hundred-seventy-six PKGPB students chosen randomly and conveniently from three universities namely the University of Tun Hussein Onn Malaysia (UTHM), University of Malaysia Sabah (UMS), and International Islamic University Malaysia (IIUM). The findings are presented in frequency and percentage form. The result of the descriptive statistics showed that majority of headteachers had a positive perception of practicing transformational leadership and they seemed to have an average level on their perception. This could mean that the school headteachers had a positive attitude toward the importance of practicing of four dimensions of transformational leadership. Especially, the dimension of creating productive school culture was found significant. Noticeably, the dimension of providing intellectual stimulation was perceived least significant by respondents.